Antioxidant Potential, Phenolic Content, and Nitrate/Nitrite Content in Various Lettuce Varieties - Pumnuan, Jarongsak; Kramchote, Somsak; Sarapothong, Kritima; Doungnapa, Thanaporn; Pisutpiboonwong, Nattakarn; Suwor, Patcharaporn (AGRIVITA Journal of Agricultural Science, 2024)
Ten lettuce varieties are analyzed for antioxidant activity, total phenolic, nitrate, and nitrite contents, and the effects of harvest maturity and cold storage in selected varieties are determined. Antioxidant activity and total phenolic content (TPC) are the highest in Red Oak, Red Coral, Red Rapids, and Grand Rapids; intermediate in Green Oak, Green Cos, and Frillice Iceberg; and the lowest in Butterhead, Mini Green Cos, and Head lettuce. Nitrate content is the highest in Red Coral, while the other 9 varieties have comparably lower contents. Nitrite content is inadequate and does not differ with variety. Harvest maturity of 45 days after transplanting (DAT) produced the highest antioxidant activity and TPC, much higher in Red Bowl and Red Butterhead varieties than in Mini Green Cos, Butterhead, Frillice Iceberg, and Green Big Bowl varieties. Storage at 8oC for 21 days has no remarkable effects on antioxidant activity, TPC, nitrate, and nitrite contents. Stored Red Bowl lettuce has higher antioxidant activity and TPC than Butter-head and Green Big Bowl varieties. Nitrate content decreases at the end of storage, while nitrite content is below 1 mg/kg FW during the entire storage period, regardless of variety.